Membuat Kelas Kreativitas di SDN 106840 KP. Benar Desa Kota Pari - Abdullah Nasution; Asrah Nabila Purba; Qori Aulia Hafni Nasution; Winda Winata S Pane; Yulia Nasution; Ella Andhany (Indo Publishing, 2026)
This research aims to explore activities at SDN 106840 KP school. It’s true that Kota Pari Village includes teaching activities, creating inspiration classes, creativity classes, role play classes, social service and arts and culture classes. Teaching at the school focuses on improving students’ academic abilities through innovative teaching methods. Inspiration and creativity classes aim to encourage students to think out-of-the-box and develop their skills in various fields. Role play classes help students hone communication and empathy skills through simulating real situations. Social service fosters students’ sense of social responsibility by involving them in community activities. Cultural arts classes introduce students to the rich culture and arts that exist in their environment, and strengthen their cultural identity. The research results show that these activities have a positive impact on students’ academic and personal development. And the method used in this research is a descriptive qualitative method using direct field observation, interviews and documentation as data collection techniques. The data analysis used is data analysis, namely data reduction, data presentation, and drawing conclusions or data verification. And the results of the research that we got were students of grade IV elementary school 106840 Kp.Benar Village Kota Pari. The level of creativity of grade IV students of SD 106840 was still very low, this was because the lessons were less interesting and the aim of our research was to increase creativity, concentration and productivity. , independence, accuracy, perseverance, as well as neatness and student skills